Equitable Reward with Job Satisfaction for Non-Management Employees - Mohammad Irfan Laxmana; Ramon Ananda Paryontri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Employee job satisfaction is an important thing in the company to create positive conditions in the organizational environment. In addition to providing benefits for employees, the company also benefits through increased production and reduced costs incurred in the company's operations by improving the attitude and behavior of its employees. Thus, work is one of the ways to achieve employee satisfaction by providing fair rewards to employees. If the salary is perceived as fair based on job demands, individual skill levels and salary standards that apply to certain job groups, then there will be job satisfaction. This study aims to determine the relationship between equitable rewards and job satisfaction of non-management employees at Al-Islam Hospital H.M. Mawardi. This research is quantitative research with a correlational method. The data collection technique used the Job Satisfaction Survey scale and the equitable reward scale taken from the equitable reward aspects. Spearman's correlation results show a significant correlation between equitable rewards and job satisfaction (r=0.571, p<.001). the magnitude of the effect of equitable reward on satisfaction is high (r=0.571). The higher the equitable reward, the higher the level of employee job satisfaction. Even reward can explain 32.6% of the variance of job satisfaction, which means that there is still 67.4% of the influence of other factors not seen in this study.Kepuasan kerja karyawan merupakan hal penting dalam perusahaan agar tercipta kondisi positif dalam lingkungan organisasi. Selain memberikan keuntungan bagi karyawan, perusahaan juga mendapatkan keuntungan melalui peningkatan produksi dan pengurangan biaya yang dikeluarkan dalam operasional perusahaan dengan adanya perbaikan sikap dan tingkah laku karyawannya. Dengan demikian salah satu cara untuk mewujudkan kepuasan kerja karyawan dengan memberikan reward yang adil kepada karyawan. Jika gaji dipersepsikan adil didasarkan tuntutan-tuntutan pekerjaan, tingkat keterampilan individu dan standar gaji yang berlaku untuk kelompok pekerjaan tertentu, maka akan ada kepuasan kerja. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara equitable reward dengan kepuasan kerja pada karyawan non manajemen di RSU Al-Islam H.M. Mawardi. penelitian ini merupakan penelitian kuantitatif dengan jenis metode korelasional. Teknik pengumpulan data menggunakan skala Job Satisfaction Survei dan skala equitable reward yang diambil dari aspek-aspek equitable reward. hasil Korelasi Spearman’s menunjukkan korelasi yang signifikan antara equitable reward dan kepuasan kerja (r=0.571, p<.001). Besaran efek equitable reward terhadap kepuasan kerja tergolong tinggi (r=0.571). Semakin tinggi equitable reward maka semakin tinggi tingkat kepuasan kerja karyawan. Equitable reward dapat mejelaskan sebesar 32.6% dari varians kepuasan kerja yang artinya masih terdapat 67,4% pengaruh dari faktor lain yang tidak terlihat dalam penelitian ini.